(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2019)
The objective of the investigation was to evaluate three lines of medium duration /10194, 9677 and 10721 under the effect of the levels 0, 60,101.49 and 144 kg of nitrogen /ha and IACuba – 30 variety was used as a check, the trial was conducted during 2014/2015 dry season a bifactorial design randomised in blocks with 16 variants nitrogen – variety with four replications was used as well as an Hydromorphic antropic, Gley soil in dept, soil samples were taken to 0-20 cm of dept. sowing was done in drill in furrows separated to 15 cm. Phosphorous and potassium were applied to 100 and 60 kg/ha, and the nitrogen was spplitted in four applications according to the treatment established. A favourable agronomic efficiency was reached with the use of nitrogen with the levels of 60,101.49 and 144 kgnitrogen/ha. Favourable economic results and net returns of 34193.2 and 34394.4 /ha, allowing corroborate that the practical application in the productive sphere is based in agronomic application in the productive sphere is based in agronomic and economically